Morbidity among iron ore mine workers in Goa - Annet Oliveira; Jagdish Cacodcar; D D Motghare (Wolters Kluwer Medknow Publications, 2014)
This study was carried out among workers from an open-cast iron ore mine in South Goa with an objective to assess morbidity among these workers. Investigations were carried out at the Occupational Health Service Clinic of the mining company. Nearly 0.6% workers had pneumoconiosis, 3.2% had abnormal spirometry findings, 38.16% had hearing loss and 27.7% had defective vision respectively. The prevalence of other chronic diseases were as follows: diabetes 5.1%, hypertension 8.3%, dyslipidemia 37.5% and polycythemia 12.7% respectively. Since the findings were not compared with the pre-placement records and as most of the workers are young with duration of exposures <10 years, relationship cannot be definitely determined. The study findings are suggesting an association between the occupation in mining with pneumoconiosis, compromised lung function and hearing loss. However for the other finding further analytical studies are required to see for any association. Airborne respirable dust survey and noise monitoring studies also need to be carried out.